Interventions and Manipulations of Interoception. Issue 1 (January 2021) - Weng, Helen Y.; Feldman, Jack L.; Leggio, Lorenzo; Napadow, Vitaly; Park, Jeanie; Price, Cynthia J.
Abstract : Interoceptive pathways may be manipulated at various levels to develop interventions to improve symptoms in a range of disorders. Primarily through the lens of the respiratory system, we outline various pathways that can be manipulated at neural, behavioral, and psychological levels to change the representation of and attention to interoceptive signals, which can alter interconnected physiological systems and improve functioning and adaptive behavior. Interventions can alter interoception via neuromodulation of the vagus nerve, slow breathing to change respiratory rate and depth, or awareness processes such as mindfulness-based interventions. Aspects of this framework may be applied to other physiological systems and future research may integrate interventions across multiple levels of manipulation or bodily systems. Highlights: Neuromodulation can tap into known interoceptive pathways for clinical benefit. Meditation with sustained interoceptive focus on breath sensations increases the neural activation of interoception networks (including insula) and decreases engagement of the default mode network, which supports self-referential processing. While sympatholytic medications often have intolerable side effects, interoceptive interventions may be a safe and well-tolerated modality to improve sympathetic regulation and thereby reduce the risk of hypertension and cardiovascular disease. Recent findings highlight possible underlying mechanisms of improved interoceptive awareness skills and emotion regulation in mindfulness-based interventions for the treatment of physical and mental health conditions.